Flexural Behaviour of Reinforced Concrete Beams with Openings Strengthened by Textile Reinforced Concrete (TRC) Wrap - Abdul Hamid, Noor Azlina; Salleh, Norhafizah; Mohd Nasir, Nur Inanisha (International Journal of Sustainable Construction Engineering and Technology, 2020)
This paper presents an experimental study of reinforced concrete beams with circular and square openings at the flexure zone. Selected beams were strengthened using Textile Reinforced Concrete (TRC) wraps. A total of six beam specimens measuring 250 mm (height) x 200 m (width) x 1700 mm (length) were cast using high strength concrete with a compressive strength of 64 N/mm2. The beams tested consisted of a solid control beam, unstrengthened concrete beams with openings and strengthened concrete beams with openings. The effect of circular and square openings on the flexure zone of concrete beams was investigated. All the beams were simply supported and tested up to failure under four-point loading. From the test results, it was found that the presence of openings at the flexure zone significantly reduces the strength and stiffness of the beams. The use of TRC wrap around the beam openings increases the ultimate capacity and stiffness of the beams. In addition, it also reduces excessive vertical cracks and deflection in beams considerably compared to unstrengthened concrete beams with openings.